Formulation of a basic tourist and recreational framework of the Tyumen region - Podryadchikova Ekaterina; Podkovyrova Marina; Kucherov Dmitry (BIO Web of Conferences)
The article presents the results of research on the principles, factors and conditions for building a basic tourist and recreational framework and its purpose in the system of rational nature management and socio-economic development of the region. The purpose of the study is to frame the sustainable development of the territory of municipal districts, ensuring the maximum possible preservation of the state of the natural and territorial complex in the formation of a territorial model of the tourist and recreational framework. The Tyumen Region has been accepted as an object of research and approbation.